Ronald Hutton, The Witch: A History of Fear, from Ancient times to the Present - York, Michael (Journal for the Study of Religion, Nature and Culture, 2018)
Ronald Hutton, The Witch: A History of Fear, from Ancient times to the Present (New Haven & London: Yale University Press, 2017), 376pp., £25 (hbk), ISBN: 978-0-3002-2904-2.